Global education in practice: Indonesian students explore the faculty of pharmacy at iTM Bertam / Nurul Alyaa Ibrahim - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2024)
On May 3, 2024, the Faculty of Pharmacy at UiTM Bertam welcomed four international students from Universitas Muhammadiyah Malang, Indonesia, for a 25-day educational exchange program. These students are pursuing Bachelor of Pharmacy degrees, with two of them in Semester 6, Year 3, and the remaining two in Semester 4, Year 2. The main purpose of this attachment is to expose the students with pharmacy education system in Malaysia and the facilities available at the faculty. Given the different educational backgrounds of our students (UiTM Bertam offers a Diploma in Pharmacy), it is important for the faculty to provide a comprehensive learning experience for these visiting students.